Concept (間) MA: Philosophical Identification and Analysis in Animated Films Howl’s Moving Castle (2004) - Yudhanto, Sigied Himawan; Setyawan, Alfan (Journal of Urban Society's Arts, 2024)
In the context of Japanese film, MA is an important concept to highlight because of its great influence on filmmaking and audience experience. In the visual arts, “MA” can be interpreted as “space” or “interval”; MA can also be said to be the core of aesthetic principles. The purpose of this study is to find and identify the philosophical aspects of the concept of MA in the scenes found in the animated film Howl’s Moving Castle (2004) to gain an understanding of visual aesthetics as well as to understand how the concept of MA works and is used in the visual aesthetics of Ghibli animated films. The research methodology on the concept of MA involves a multidimensional approach that includes visual language methods, literature study, and content analysis, as well as a combination of theories on emptiness and tensegrity structure. The analysis shows that the number of scenes containing MA factors is 17 scenes; the total scenes in the movie are about 2,301 scenes, with the assumption that each scene averages 3 seconds. The 17 scenes only take up a portion of 0.73%, a relatively flat number; then, if we take the duration of time for each scene, a value shows the total scene that contains MA factors is 333 Seconds or 5.55 minutes while the total duration of the Howl’s Moving Castle animated film is 01:55:05 minutes or about 6,905 seconds the MA transition scene is 4.8% of the total film. The research can provide an in-depth insight into the use of MA in the context of animated films, where it can provide an understanding of how seemingly simple visual elements, such as empty space, can have a strong impact on the audience’s experience and level of engagement, or understanding of the story and characters. Dalam konteks film Jepang, MA merupakan konsep yang penting disorot karena pengaruhnya yang besar terhadap pembuatan film dan pengalaman penonton. “MA” dapat diartikan sebagai “ruang” atau “interval”, yang juga sebagai inti dari prinsip estetika. Tujuan dari penelitian ini adalah mencari dan mengidentifikasi aspek filosofis, konsep MA pada scene yang terdapat pada film animasi Howl’s Moving Castle (2004) untuk mendapatkan pemahaman tentang estetika visual sekaligus untuk memahami bagaimana konsep MA bekerja dan digunakan dalam estetika visual film-film animasi Ghibli. Metodologi penelitian tentang konsep MA melibatkan pendekatan multidimensi yang mencakup metode bahasa visual, studi literatur dan analisis konten, serta kombinasi teori tentang emptiness dan tensegrity structure. Analisis menunjukan banyaknya scene yang mengandung MA factor adalah 17 scene, total scene dalam film ada sekitar 2,301 scene dengan durasi rata-rata setiap scene sebesar 3 detik. 17 scene tersebut hanya memakan porsi sebesar 0.73 %, dengan total scene yang terdapat MA faktor sebanyak 333 Second atau 5.55 menit sedangkan total dari durasi film animasi Howl’s Moving Castle sebanyak 01:55:05 menit atau sekitar 6,905 detik maka scene transisi MA sebesar 4.8 % dari total keseluruhan film. Penelitian ini dapat memberikan wawasan mendalam tentang penggunaan MA dalam konteks film animasi, dimana hal tersebut dapat memberikan pemahaman bagaimana elemen-elemen visual yang tampak sederhana, seperti ruang kosong, dapat memberikan dampak yang kuat terhadap pengalaman penonton dan tingkat keterlibatan, atau pemahaman penonton terhadap cerita dan karakter.